2002
DOI: 10.1079/joh200191
|View full text |Cite
|
Sign up to set email alerts
|

Affinities between Asian non-humanSchistosomaspecies, theS. indicumgroup, and the African human schistosomes

Abstract: Schistosoma species have traditionally been arranged in groups based on egg morphology, geographical origins, and the genus or family of snail intermediate host. One of these groups is the`S. indicum group' comprising species from Asia that use pulmonate snails as intermediate hosts. DNA sequences were obtained from the four members of this group (S. indicum, S. spindale, S. nasale and S. incognitum) to provide information concerning their phylogenetic relationships with other Asian and African species and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…Most recent studies have added gene fragments or additional taxa to particular clades within Schistosoma to test the position of individual taxa (e.g. Agatsuma et al 2001Agatsuma et al , 2002Blair et al 1997), or to examine some of the biogeographic hypotheses suggested by Snyder & Loker's (2000) scheme, e.g. Zhang et al (2001) and Attwood et al (2002 b).…”
Section: Taxonomy and Systematicsmentioning
confidence: 99%
“…Most recent studies have added gene fragments or additional taxa to particular clades within Schistosoma to test the position of individual taxa (e.g. Agatsuma et al 2001Agatsuma et al , 2002Blair et al 1997), or to examine some of the biogeographic hypotheses suggested by Snyder & Loker's (2000) scheme, e.g. Zhang et al (2001) and Attwood et al (2002 b).…”
Section: Taxonomy and Systematicsmentioning
confidence: 99%
“…Amongst the four recognised common Schistosoma species groups [3], the Schistosoma indicum species group has received less attention than its congeners since none of these species ultimately infect humans in the final stage of their life cycle [46]. However, it remains responsible for severe outbreaks of cattle schistosomiasis and human cercarial dermatitis in India and Southeast Asia [2, 7–12].…”
Section: Introductionmentioning
confidence: 99%
“…Although Schistosoma incognitum was formerly included in this group, it has been shown that it is a more distant relative (Agatsuma et al, 2002; Attwood et al, 2002; Morgan et al, 2003; Webster et al, 2006: Lawton et al, 2011). Among the four customarily recognized and prominent species groups, our overall knowledge of the S. indicum group lags far behind the other three.…”
Section: Introductionmentioning
confidence: 99%
“…Adult males of this species have prominent tubercles, most of which lack spines (Southgate et al, 1990). This species is known from India, Bangladesh, Myanmar and Sri Lanka (Dutt, 1967; Rollinson and Southgate, 1987; Agatsuma et al, 2002; Lockyer et al, 2003; Attwood et al, 2007). …”
Section: Introductionmentioning
confidence: 99%